UJI PREFERENSI KONSUMEN TERHADAP KARAKTER BUNGA KEMBANG KERTAS (Zinnia elegans Jacq.) - Aziz Purwantoro; Jamhari (Program Studi Agroteknologi INSTIPER, 2017)
Zinnia elegans Jacq. are found in Indonesia, but in general these plants have a less attractive appearance. Efforts to developed Zinnia elegans Jacq. need to be done so that it can be used as cut flowers besides Chrysanthemum. Method of cultivation have been obtained in producingflower seeds (first year) the next step is testing the quality of the character of the shape of flowers and consumers preference test. It was necessary to be able to ensure that flowers produced have good quality and can have economic value. Experiment was conducted to test consumer preferences for phenotypic characters on Zinnia elegans Jacq. flower plant populations generation M5 and M6 result of X-ray irradiation. Preference test was through questionnaire survey method. Results of the assessment Respondents were then tested using Friedman Test / Two-Way ANOVA by rating (Two-way ANOVA by ranks) with SPSS software. The results showed that the type of pompom flowers was preferred than a single type (single). Respondents were also prefer flowers that are not too high, flower with widediameter, and flowers with more fragrant. Flower color preferences based on analysis of respondents in a row is red, purple, white, and yellow.